Start-up intensity, competition and regional economic development - Sierdjan Koster; André Van Stel; Mickey Folkeringa (European Regional Science Association (ERSA), 2010)
We investigate the impact of start-up rates on regional economic development. We argue that in line with Schumpeter's view this effect is mediated by a process of creative destruc-tion: Start-ups spark a process of creative destruction which in turn leads to regional eco-nomic development. Koster et al. (2010) investigate the former relationship. This paper fo-cuses on the latter. Interactions between new and incumbent firms play an important role in the process of eco-nomic growth, and more knowledge on these interactions is required. Our paper fits in a re-cent strand of empirical research at the regional level (see Fritsch, 2008, for a survey) which suggests that competition among incumbent firms is caused by (lagged) start-up rates. Contrary to earlier research the present paper employs a direct measure of the level of competition between incumbents, which is called mobility (Cantner and Krüger, 2004). The mobility rate measures to what extent the relative performance of firms (with respect to each other) in a market changes over time. Based on Joseph Schumpeter's theory of creative destruction we hypothesise that the mobility rate positively influences regional economic development. New firms challenge existing firms by introducing new products and services and market selection will cause the best firms to survive and grow and the least competitive firms to downsize or exit. In the present paper we test our hypothesis by estimating a regression model at the region-sector level for the Netherlands, where regional economic development (employment growth) is explained by the mobility measure, (lagged) startup rates and control variables. In order to mitigate endogeneity problems we adopt a 2SLS approach.
Keywords: O18; L16; M13; 330; start-ups; incumbent firms; competition; market mobility; employment growth